Cancer-associated fibroblasts in pancreatic adenocarcinoma. (September 2015) - Pan, Boju; Liao, Quan; Niu, Zheyu; Zhou, Li; Zhao, Yupei
Pancreatic ductal adenocarcinoma (PDAC) is one of the most highly malignant tumors with a very poor prognosis. In addition to the cancer cells, the stroma of tumor can expand by 50% and influence cancer cell growth. Cancer-associated fibroblasts (CAFs) are important components of tumor stroma. Cancer cells, normal fibroblasts, normal epithelial cells as well as bone marrow-derived myofibroblasts contribute to the emergence of CAFs through various cytokines (e.g., TGF-β, SHH, PDGF) and epithelial-to-mesenchymal transition. CAFs affect cancer growth, survival, metastasis, angiogenesis and immunosurveillance through the secretion of various cytokines, such as CXCL12 and secreted protein acidic and rich in cystein. Also, CAFs correlate to the prognosis and chemoresistance of PDAC patients. As novel therapeutic targets, CAFs, and their relative factors, represent an important role in PDAC therapy.